Dinamika Perdagangan Halal (Mekanisme Pasar Sebagai Mesin Inovasi) - Wahyu Ningtyas, Dwi; Toyibah, Askin (Musyarakah: Journal of Sharia Economic (MJSE), 2024)
This study explores the dynamics of halal trade through market mechanisms as an engine of innovation using a qualitative method with literature analysis. The main focus is to understand how market mechanisms function as a catalyst for innovation in halal trade. This research collects and analyzes data from various literature sources, including academic journals, industry reports, and government publications, to identify key patterns and trends. The analysis results show that strict regulations and clear certification standards play an important role in driving product and process innovation in the halal industry. Additionally, the literature indicates that the adoption of technologies such as blockchain and the Internet of Things (IoT) has enhanced transparency and efficiency in the halal supply chain. The study also finds that increasing consumer preferences for halal products drive companies to innovate to meet dynamic market demands. The conclusion of this study highlights the importance of synergy between regulations, technology, and market dynamics in fostering innovation in the halal sector. Policy recommendations and practical implications are presented to support the sustainable and competitive growth of halal trade.